Effect of two additional doses of intrathecal methotrexate during induction therapy on serious infectious toxicity in pediatric patients with acute lymphoblastic leukemia - Heilmann, Janina; Vieth, Simon; Möricke, Anja; Attarbaschi, Andishe; Barbaric, Draga; Bodmer, Nicole; Colombini, Antonella; Dalla-Pozza, Luciano; Elitzur, Sarah; Izraeli, Shai; Mann, Georg; Niggli, Felix; et al. (Haematologica, 2023)
Although initial central nervous system (CNS) involvement is rarely detected in childhood acute lymphoblastic leukemia (ALL), risk-adapted CNS-directed therapy is essential for all patients. Treatment intensity depends on the initial CNS status. In the AIEOP-BFM ALL 2009 trial, patients with cytomorphologic detection of leukemic blasts in initial cerebrospinal fluid were classified as CNS2 or CNS3 and received five intrathecal doses of methotrexate (MTX) in induction therapy compared to patients with CNS1 status (no blasts detected) who received three doses. The impact of additional intrathecal (IT) MTX on systemic toxicity in induction therapy is unknown. Between June 1st 2010 and February 28th 2017, a total of 6,136 ALL patients aged 1-17 years were enrolled onto the AIEOP-BFM ALL 2009 trial. The effect of three versus five doses of IT MTX during induction therapy on the incidence of severe infectious complications was analyzed. Among 4,706 patients treated with three IT MTX doses, 77 (1.6%) had a life-threatening infection during induction as compared to 59 of 1,350 (4.4%) patients treated with five doses (P<0.001; Odds Ratio 2.86 [95% Confidence Interval 1.99-4.13]). In a multivariate regression model, treatment with additional IT MTX proved to be the strongest risk factor for life-threatening infections (Odds Ratio 2.85 [1.96-4.14]). Fatal infections occurred in 16 (0.3%) and 38 (1.6%) patients treated with three or five IT MTX doses, respectively (P<0.001). As the relevance of additional intrathecal MTX in induction for relapse prevention in CNS2 patients is unclear, doses of intrathecal therapy have been reduced for these patients. (Clinicaltrials.gov identifiers: NCT01117441 and NCT00613457).
Keywords: lidé; kombinovaná terapie; Induction Chemotherapy; Antineoplastic Combined Chemotherapy Protocols; dítě; Child; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Methotrexate; protokoly protinádorové kombinované chemoterapie; methotrexát; indukční chemoterapie; akutní lymfatická leukemie; Humans; Combined Modality Therapy